Should a 31/62-day target be applicable to urinary stone patients with indwelling stents?. (January 2015) - Smith, T; Gruber, M; Simoes, A; Krishnan, R; Shrotri, N
Objective: Patients with urinary stone disease languish on waiting lists. They are often young and suffer morbidity and unemployment. Stone disease leads to sepsis, loss of renal units and even death. We aimed to assess the readmission rates and associated morbidity for patients with ureteric stents in situ secondary to stone disease. Patients and methods: Over 12 months 692 patients totalling 1114 admissions were admitted to our unit with a coded diagnosis of renal colic. Of the 692 individuals, 378 first presented as an emergency. The rest had elective first admissions. Results: Of the 378 emergency presentations, 78 were admitted between two and eight times. The total number of admissions for this group of 78 patients was 248. The average time interval was calculated from first emergency presentation to date of first elective treatment (52.3 days (range 2–281)) and from date of first emergency presentation to date of last treatment (63.6 days (range 2–281)). A total of 401 working days were lost. Conclusion: The management of patients with urinary stone disease needs serious reconsideration. We propose that patients with indwelling stents have a 31/62-day target similar to cancer patients due to the increased morbidity associated with loss of working days and the increased cost of readmissions to an overburdened health service.